Case Report : Nephrotic Syndrome - Devi Gusmaiyanto; Destri Linjani (The International Science of Health Journal, 2024)
Nephrotic syndrome (NS) is characterized by persistent heavy proteinuria (mainly albuminuria) (>2 g/m2/24 hours); hypoproteinemia (serum albumin 250 mg/dL); and edema. Small amounts of protein are found in the urine of healthy children. Nephrotic syndrome is an important chronic disease in children. The estimated annual incidence of nephrotic syndrome in healthy children is two to seven new cases per 100,000 children under 18 years of age. A case has been reported of a boy aged 9 years 5 months who was brought by his parents to the emergency room at Tengku Rafi'an Siak District Hospital with complaints of swelling since 2 days ago before being admitted to the hospital. Complaints accompanied by puffy eyes when waking up, urinating a little, stomach and legs feeling like they are getting bigger. History of the same complaint (+), diagnosed with nephrotic syndrome in February 2024. Children with first clinical manifestations of SN should be hospitalized in order to accelerate examination and evaluation of dietary management, edema management, initiation of steroid treatment, and parental education.